Integrating potato in farming systems for food and nutritional security - Kumar, Manoj; Rawal, Sanjay (Indian Horticulture, 2019)
Marginal and small farmers, representing more than 86% of Indian farm families with a land holding size below 1.2 ha are living in risk-prone diverse production conditions. Doubling their income by 2022 is a challenge. Integrated farming systems is an answer to this problem. High yield potential, nutritional quality, flexibility of crop duration and timing serves potato crop as one of the best options to fit into several farming systems in different agro-ecologies. Potato is remarkably potential component crop for emerging farming systems in different regions of the country. It will certainly improve the productivity and farm profits for small farmers.